2013
DOI: 10.3892/ol.2013.1226
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 and CD100 immunohistochemical expression is associated with local recurrence and poor prognosis in soft tissue sarcomas, respectively

Abstract: Soft tissue sarcomas (STSs) are a heterogeneous group of mesenchymal tumors of >50 subtypes. However, STSs represent <1% of types of cancer. Despite this low frequency, the disease is aggressive and treatment, when possible, is based on traditional chemotherapies. A number of cases of resistance to adjuvant therapies have been reported. Metastases are commonly identified in STS patients during diagnosis and the development of effective clinical parameters is crucial for correct management of the disease. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
(37 reference statements)
3
16
0
Order By: Relevance
“…232 Regardless of the mechanisms involved, there are numerous observations suggesting that sema4D plays a stimulatory role in the progression of several types of tumors including head and neck tumors, breast carcinomas, ovarian cancinomas, pancreatic carcinoma, prostate cancer and soft tissue sarcomas such as osteosarcoma. [233][234][235][236][237][238][239] These observations lead to the development of inhibitory humanized antibodies that are developed as anti-tumorigenic drugs that target sema4D. 240 However, there are also opposite observations.…”
mentioning
confidence: 99%
“…232 Regardless of the mechanisms involved, there are numerous observations suggesting that sema4D plays a stimulatory role in the progression of several types of tumors including head and neck tumors, breast carcinomas, ovarian cancinomas, pancreatic carcinoma, prostate cancer and soft tissue sarcomas such as osteosarcoma. [233][234][235][236][237][238][239] These observations lead to the development of inhibitory humanized antibodies that are developed as anti-tumorigenic drugs that target sema4D. 240 However, there are also opposite observations.…”
mentioning
confidence: 99%
“…SEMA4D has both a cellular, membrane-bound form (cSE-MA4D) and a biologically active soluble ligand (sSEMA4D) generated by cleavage of the cellular form (13). Immunohistochemical analysis of SEMA4D demonstrated that both the cellular and soluble forms are overexpressed on several tumor types, including breast, pancreatic, colon, ovarian, urogenital, and head, and neck (14), with overexpression correlating with poor prognosis in sarcomas and pancreatic cancer (6,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) analysis of several tumor types revealed that both SEMA4D and its receptors are overexpressed on various human and murine tumors, including human head and neck, prostate, colon, breast, and lung cancers (20). Moreover, elevated expression correlates with invasive disease and poor prognosis in human cancer (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%